Deir Anba Hadra, Ägypten: Koptische und arabische Inschriften sowie archäologisch-bauforscherische Untersuchungen im Simeonskloster bei Assuan - Richter, Sebastian (e-Forschungsberichte des DAI, 2023)
In March 2013 an epigraphic survey at the medieval site of Dayr Anba Hadra and its environs on the West bank of Aswan was conducted. Its aim was to gain a general idea of the Coptic epigraphic activity in the wider area of Aswan, to record the Coptic graffiti and dipinti of the 10th to 14th century CE within the monastery, and to develop a research schedule for future investigation of this site at a larger scale and with a wider scope than merely its epigraphic evidence.